2013
DOI: 10.1681/asn.2012090908
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Membrane Permeability and Dialysate Purity on Cardiovascular Outcomes

Abstract: The effects of high-flux dialysis and ultrapure dialysate on survival of hemodialysis patients are incompletely understood. We conducted a randomized controlled trial to investigate the effects of both membrane permeability and dialysate purity on cardiovascular outcomes. We randomly assigned 704 patients on three times per week hemodialysis to either high-or low-flux dialyzers and either ultrapure or standard dialysate using a two-by-two factorial design. The primary outcome was a composite of fatal and nonfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…Secondly, recent advance in hemodialysis may enable twiceweekly HD to maintain for a long-term dialysis vintage. Most patients in the study used Fresenius high flux dialyzers and all the patients used ultrapure dialysate, such conditions would ensure an optimal solute clearance and benefit both the twice-weekly HD and thriceweekly HD patients [19][20][21]. Thus, our unique twice-weekly HD model characterized as a longer HD session time, a higher spKt/V around 2.0, and using high flux dialyzers and a personalized incremental dialysis approach.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, recent advance in hemodialysis may enable twiceweekly HD to maintain for a long-term dialysis vintage. Most patients in the study used Fresenius high flux dialyzers and all the patients used ultrapure dialysate, such conditions would ensure an optimal solute clearance and benefit both the twice-weekly HD and thriceweekly HD patients [19][20][21]. Thus, our unique twice-weekly HD model characterized as a longer HD session time, a higher spKt/V around 2.0, and using high flux dialyzers and a personalized incremental dialysis approach.…”
Section: Discussionmentioning
confidence: 99%
“…While survival remains much higher in Japan than in other countries, further improvement should always be sought, and public policy planners should be aware that stabilization in the prevalent population is, in reality, a sign that new efforts to improve dialysis survival must be supported. Perhaps technological advancements such as the use of ultrapure dialysis [17][18][19] might conceivably result in gains in prevalent patient survival. Additionally, the Japanese research community should continue to investigate whether increasing the use of β-adrenergic blockers, which may benefit some patients [20,21] and which are used in comparatively lower amounts in Japan than in some other countries [22], could provide longevity benefits, especially in patients with heart failure or left ventricular hypertrophy.…”
Section: Health Trends In Esrdmentioning
confidence: 99%
“…A systematic review found a significant benefit of ultrapure dialysis fluid [28] and a recent controlled trial found a lower ESA dose usage in 85 patients randomized to ultrapure fluid [29] . In our study, all treatments were performed with dialysis machines having on-line ultrafiltration of dialysis fluid.…”
Section: Discussionmentioning
confidence: 99%